Incisor trauma and the planning of orthodontic treatment - Bender, Birgit; Zeh, Debora; Wörtche, Eva (Journal of orofacial orthopedics, 2006)
Because of the frequency of dental injuries during infancy and adolescence, traumatized teeth with variable long-term prognoses present a problem for orthodontic treatment planning. Orthodontic therapy can remain unaffected, or be complicated, by traumatized teeth. In some cases, following dental injury, orthodontics can also be used to enhance (prosthetic and) restorative treatment results. The orthodontic challenges involved in treating patients with a history of dental trauma are complicated by the consequences of trauma on dentition development and the different treatment options that must be considered. In this paper, we provide actual examples of the effects dental trauma can have on orthodontic treatment planning.
Gesehen am 10.03.2021